Freudiaans-antropologiese vooronderstellings in die neo-Marxistiese skool- en maatskappykritiek - Coetzee, Daniella (Koers, 1994)
Dissatisfaction with education in South Africa has given rise to diverse and politically radical school criticism. The educational views of anti-establishment schools of thought (eg. Marxism-Leninism, neo-Marxism, Contraculture, New Age Movement and the ideas of Paolo Freire) are extremely relevant to the current situation of education in South Africa. This article therefore emphasizes specific anthropological suppositions underlying neo-Marxist culture and critique of society. Although Marxist influence on Emancipatory Education is acknowledged, emphasis is placed on Freudian roots of the neo-Marxist view on education. The influence of the Freudian personality theory on a selection of relevant themes, such as oppression in a capitalist society; politization of education; religion and repression of instincts is underlined. In conclusion it is shown that a school of thought that is based on deterministic suppositions abounds with inherent difficulties and can be regarded as educationally unsound.